2021
DOI: 10.1172/jci.insight.146973
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling identifies impaired adaptive NK cells expanded after HCMV reactivation in haploidentical HSCT

Abstract: Haploidentical hematopoietic stem cell transplantation (h-HSCT) represents an efficient curative approach for patients affected by hematologic malignancies in which the reduced intensity conditioning induces a state of immunologic tolerance between donor and recipient. However, opportunistic viral infections greatly affect h-HSCT clinical outcomes. Natural Killer (NK) cells are the first lymphocytes recovering after transplant and provide a prompt defense against human Cytomegalovirus (HCMV) infection/reactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 65 publications
5
34
0
Order By: Relevance
“…Expression of CD57, a marker of late differentiation, was somewhat lower in the first month post-reactivation but then increased continuously over subsequent months. As such, the classical expression of CD57 and KIR on adaptive memory NK cells is seen to develop late after reactivation 38 and supports evidence for coupling of differentiation and proliferation of NK cells over an extended period 39,40,28 . It is not clear why expression was reduced during the first month after reactivation although this may reflect preferential recruitment of this subset into tissue.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Expression of CD57, a marker of late differentiation, was somewhat lower in the first month post-reactivation but then increased continuously over subsequent months. As such, the classical expression of CD57 and KIR on adaptive memory NK cells is seen to develop late after reactivation 38 and supports evidence for coupling of differentiation and proliferation of NK cells over an extended period 39,40,28 . It is not clear why expression was reduced during the first month after reactivation although this may reflect preferential recruitment of this subset into tissue.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, this increase was accompanied by a reduction in the NK cell percentage within the peripheral repertoire and reflects the profound impact of CMV reactivation on expansion of other lymphoid subsets, most notably T cells 26 . The nature of HSCT transplant conditioning and donor choice is likely to impact substantially on the profile of NK reconstitution and similar findings have been seen after umbilical donor transplantion 24 although an increase in NK number was not seen in the setting of haploidential transplantation 27,28 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…An emerging report from Elisa Zaghi et al demonstrated impaired adaptive NK cells expanded after CMV reactivation in PTCy-haploSCT (97). By a longitudinal single-cell computational profiling of multiparametric flow cytometry, they found that CMV accelerates NK cell immune recovery with the expansion of CD158b1b2j pos /NKG2A neg /NKG2C pos / NKp30 lo NK cells.…”
Section: Nkmentioning
confidence: 98%
“…Therefore, enhancing CMV-specific CTL and NK cell recovery represents a future direction for virus infection prevention, including CMV, EBV, and BKV. Unfortunately, overcoming the functional impairments of adaptive NK cells to produce IFN-g (162), a phenomenon due to the virus-induced expression of lymphocyte activation gene 3 and programmed cell death protein 1 checkpoint inhibitors, remains to be investigated. In addition, a phase II multicenter, randomized trial is ongoing to investigate the protective function of the CMV-MVA triplex vaccine in adult recipients who received haplo-SCT (NCT 04161885).…”
Section: Future Prospectsmentioning
confidence: 99%